Technologies used to capture CO2 in the steel industry: a bibliometric analysis - Aleson; Lucas Alexandre; Maristela; Ana (Latin American Journal of Energy Research, 2025)
The steel industry has a high energy demand and is responsible for significant carbon dioxide (CO2) emissions, accounting for between 7% and 9% of global emissions. Carbon Capture and Storage (CCS) technologies emerge as essential alternatives for the decarbonization of this sector, contributing to achieving net-zero emission targets by 2050. This study carried out a bibliometric and prior art analysis of technologies applied to carbon capture in steelmaking processes, using the Web of Science, Scopus, Espacenet, and Patentscope databases for the period from 2020 to 2025. A total of 492 articles and 10 relevant patents were identified, with post-combustion routes predominating, particularly those employing absorption and adsorption technologies. The results show a growing global interest in the topic, led by researchers and institutions from China, with emphasis on studies integrating computational simulations and thermoenergetic analyses. It was also found that replacing fossil fuels with biomass, combined with CCS, can achieve negative emissions. However, implementation costs, comparative efficiency among routes, and the integration of renewable energy sources still require further investment. Advances in modeling research, materials development, and incentive policies are crucial to enabling the transition of the steel industry toward a low-carbon economy.